Evaluation of Suitability and Carrying Capacity of Bolihutuo Beach for Tourism - Irni Hiola; Sitti Nursinar; Citra Panigoro (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2019)
The purpose of this study is to determine the suitability of land for shore excursions and the carrying capacity of the region in the category of recreational beach activities at the beach tourist area Bolihutuo Subdistrict Botumoito, District Boalemo. Research was conducted in February 2015 until Desember 2015. The method used in this research is descriptive and qualitative methods. Data collection techniques was to measure the suitability of beach resort that is depth, type of beach, wide beaches, basic materials waters, current speed, the slope of the beach, water transparency, the closure of beach land, dangerous biota, the availability of fresh water as well as the carrying capacity of the beach recreation namely the time spent by visitors and the time provided by the manager. The result shows that Bolihutuo is in the category of very suitable (S1) with the index value of 91%. Bolihutuo Beach has a capacity of 1998 visitor per day, with an area that can be utilized by the shoreline of about 30.000m2. Keywords: Suitability; carrying capacity; beach tourism